Determination of risk factors and patient profile in human hydatidosis - Ahmet Korul; Mustafa Köse; Sezgin Yılmaz (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out in Afyonkarahisar to determine the patient profile and to reveal risk factors in human hydatidosis (cystic echinococcosis) out in Afyonkarahisar region, Turkey. Materials and Methods: The hospital records of 166 patients diagnosed with hydatidosis and treated surgically were evaluated. The patients were subjected to a questionnaire consisting of 30 questions. Results: The incidence of hydatidosis was found to be higher in women (53%) than in men (47%). Cysts shoved the highest proportion in the liver (53%) and in the lungs (40.4%) and lowest in the brain (1.2%). Infection was exclusively concentrated between 50 and 59 (19.9%) year old patients and the lowest was in the 0-9 (2, 4%) age group. The rate was 49.1% in the elementary- secondary education group and 0.6% in the post graduate studies group. There was a close association between the incidence and patient's income. Patients had lower income (less the 10.000 TL) showed higher incidence (48.8%) whereas those having higher income (50.000 TL and over) had the lowest incidence rate (0.6%). Incidence was higher in rural residents (62%) than in urban residents (38%). Hydatidosis was found to be higher in dog owners (54.8%) than in non-dog owners (45.2%). Conclusion: Hydatidosis is considered a very important public health problem with major socio-economic impacts in countries where it is particularly endemic. Patient profiles, demographics and risk factors are extensively presented in hydatidosis, an important parasitic zoonosis that threatens public health in Turkey in this study.